Green public procurement in the academic literature - Ionela-Corina Chersan; Valentin Florentin Dumitru; C\~at\~alina Gorgan; Vasile Gorgan (Amfiteatru Economic Journal, 2020)
The study aim is to present a review of the literature dedicated to green public procurement. We analyse traditionally and using a structured literature review 115 articles indexed in Scopus on this topic. The contribution of the paper consists in the development of the knowledge regarding the green procurement in the public domain, by highlighting the main investigations in the literature and their results, identifying the limits, but also the orientation towards future research. The results indicate increased attention paid by researchers to raising awareness of the importance of green procurement and its effect on sustainable development, as well as the need to create tools for implementation by both governments and entities involved in such purchases. We believe that our paper can have an impact on practice and public purchases standards, as it crystallizes the ideas of issuing applicable and useful regulations in terms of green procurement.
Keywords: O13; Q56; 330; green public procurement; structured literature review (SLR); sustainability; environment